2015
DOI: 10.1242/dev.115931
|View full text |Cite
|
Sign up to set email alerts
|

ERBB3-mediated regulation of Bergmann glia proliferation in cerebellar lamination

Abstract: Cortical lamination is crucial for the assembly of cerebellar circuitry. In this process, granule neurons (GNs) migrate along Bergmann glia (BG), which are specialized astroglial cells, from the external granule layer to the internal granule layer. However, the molecular mechanisms underlying BG development are not well understood. Here, we show that GFAP::Cre;Erbb3 F/F mice, which lack Erbb3 in both radial glia and neurons, exhibit impairments in balance and motor coordination. Cerebellar lamination is aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Cao et al 35 ) based largely on a report of reduced autophosphorylation compared to EGFR in insect cells with induced ErbB3 expression, 36 recent studies have suggested that ErbB3 has sufficient kinase activity for signaling, 37 , 38 , 39 and its downstream signaling primarily involves PI3K/AKT. 40 ErbB3 has also recently been found to be required for certain types of cell proliferation in the brain, likely due to downstream PI3K signaling. 40 Peripheral NRG1 administration (shown to be safe in humans 41 , 42 ) increases neurogenesis, producing additional GCs expressing ErbB3, with concomitant antidepressant-like effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al 35 ) based largely on a report of reduced autophosphorylation compared to EGFR in insect cells with induced ErbB3 expression, 36 recent studies have suggested that ErbB3 has sufficient kinase activity for signaling, 37 , 38 , 39 and its downstream signaling primarily involves PI3K/AKT. 40 ErbB3 has also recently been found to be required for certain types of cell proliferation in the brain, likely due to downstream PI3K signaling. 40 Peripheral NRG1 administration (shown to be safe in humans 41 , 42 ) increases neurogenesis, producing additional GCs expressing ErbB3, with concomitant antidepressant-like effects.…”
Section: Discussionmentioning
confidence: 99%
“…S9). Because BG radial fibers provide scaffolds for GNP migration (36,42), the abnormal BG morphology and localization likely contribute to the impaired migration of GNPs and morphogenesis defects in hGFAP-Cre;Rack1 F/F mice. hGFAP-Cre and Atoh1-Cre mice, but not GLAST-CreER T2 -driven Rack1 conditional KO mice, display abnormal BG morphology.…”
Section: Ablation Of Rack1 In Multipotent Nscs Disrupts Cerebellarmentioning
confidence: 99%
“…Proliferation and migration of neural progenitor cells in the external granular layer (EGL) as well as the proliferation of immature glial cells are characteristic of late fetal and early postnatal development of the cerebellum. All of these processes are largely influenced or directed by the activity of the Purkinje cells [11][12][13] together with Bergmann Glia [14][15][16], by glia-glia [17][18][19], as well as by glia-neuron interactions [20][21][22], mainly through signaling via growth factors, chemokines and cytokines, transmitters and transcription factors. This review seeks to highlight shared mechanisms of glial cell regulation that are relevant for development and disease of the cerebellar white matter that may serve to design future strategies for protection.…”
Section: Introductionmentioning
confidence: 99%